Social Media Communication Strategy BusinessB-To-B in an Effort to Increase Customer Loyalty - Helda Rahayu Chandra (LEGAL BRIEF, 2022)
A Business-to-Business (B-to-B) operation is one that demands customer loyalty. Unlike B-To-C (Business-to-Customer) Business, B-To-B (Business-to-Business) Industry has a target market of other businesses or organizations. However, the use of social media to increase B-to-B customer loyalty is still the widely discussed topic. This study aims to determine the use of social media in B-To-B businesses in building B-To-B consumer loyalty. The research was conducted on B-To-B companies which also have a target market of business customers using descriptive qualitative methods. The results of the study indicate that communication activities on social media carried out by companies are in the form of content management, advertising, and digital activities. Companies use social media to increase consumer awareness of products or services with their advertising features, and enhance brand image by presenting content that reflects the company's image. Social media is also considered to be able to increase engagement with customers through content that is considered useful for customers. Social media communication is not done to increase customer loyalty to the company. To gain customer loyalty, the company strives to provide services or products that meet customer expectations, prices that are in accordance with customer capabilities, and the total experience gained while using the service. Social media is also considered to be able to increase engagement with customers through content that is considered useful for customers. Social media communication is not done to increase customer loyalty to the company. To gain customer loyalty, the company strives to provide services or products that meet customer expectations, prices that are in accordance with customer capabilities, and the total experience gained while using the service. Social media is also considered to be able to increase engagement with customers through content that is considered useful for customers. Social media communication is not done to increase customer loyalty to the company. To gain customer loyalty, the company strives to provide services or products that meet customer expectations, prices that are in accordance with customer capabilities, and the total experience gained while using the service.